Ecological risk assessment of organochlorine pesticides in sediment : a case study of the Chanthaburi Estuary - Napaporn Leadprathom; Preeda Pakpian; Jutamaad Sattayavivad; Chongrak Polprasert; Settachan, Daam; Ikejima, Kou; Chulabhorn Research Institute; Mahidol University; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
The Chanthaburi River of Thailand is surrounded by vast agricultural areas at its upstream whereas the downstream connecting with the estuary in which intensive aquaculture become wide spread. Such activities have been practiced for over two decades. It is believed that mixtures of toxic compounds, especially those of persistent organochlorine pesticides (OCPs) used for pest control in the farm lands might have been drifted and transferred into the river and further trapped by the sediment within the estuary. This sediment could pose potential harm to aquatic biota in the estuary area particularly through resuspension as a result of dredging of sediment. However, information of OCPs in the area is limited in terms of their behavior and toxicity for native aquatic species. Therefore, this study attempts to determine distribution of OCPs residues in the study area for determination of their environmental risks. Ecological risk was assessed on predominating OCPs in water and sediment by using the safety value from the native shrimp (Penaeus monodon) larva toxicity test and published guidelines. Additionally, OCPs removal from sediment by low density polyethylene (LDPE) plastic pellets was conducted to estimate its potential for OCPs clean up. In water samples, out of twenty OCPs determined, endosulfan and hexachlorocyclohexanes (HCHs) are the two compounds which predominated in a narrow range from 0.6-13 ng/L and 1-12 ng/L, respectively. Both compounds were found to have higher concentrations during the wet season. The two insecticides also had significant correlation with total organic carbon (TOC) in the water, with the r values of 0.571 (P<0.05) and 0.440 (P<O.1), for endosulfan and HCHs respectively suggesting that these chemicals are strongly bound and concentrated in organic carbon in the water. Endosulfan and HCHs were found to reside more in suspended particulate matter (SPM) and in the surface sediment (0-5 cm) with an average range from 25-1,219 ug/kg dry wt and 19-110 ug/kg dry wt for SPM, 4-70 ug/kg dry wt and 0.5-50 ug/kg dry wt for surface sediment, respectively; even though these chemicals have been banned in Thailand. Oyster, sea bass and shrimp from selected farms cultured at the study area seemed to uptake both endosulfan and HCHs in proportion to levels present in the water and SPM. The range of endosulfan and HCHs observed were 4-46 ug/kg wet wt and nd-8 ug/kg wet wt in oysters, 0.6-8 ug/kg wet wt and nd-7 ug/kg wet wt in seabass, nd-2.7 ug/kg wet wt and 2-13 ug/kg wet wt in shrimp. The findings from ERA (ecological risk assessment) conducted indicates that several stations had endosulfan and HCHs levels in sediments that exceeded the published guideline and the estimated safety value from the shrimp toxicity test. Thus, risks might be anticipated from dredging. However, the water body currently do not pose a risk. Low density polyethylene (LDPE) plastic pellets have the potential to remove endosulfan, which is the predominant OCPs found in sediment in this study. Results from the equilibrium study of endosulfan removal by LDPE pellets in different time intervals showed that LDPE could remove endosulfan from sediment, reaching to equilibrium within 72 hours. The removal efficiency of endosulfan was found between 44-67% in 1 cycle of removal at different concentrations studied (0.6, 1.2, 6 and 13 mg/kg). Since the study was estuarine, the effect of salinity gradients (3, 17 and 30 ppt) on endosulfan removal from sediment by LDPE pellets was evaluated. The findings indicated that at the three levels of salinity studied, endosulfan removal efficiency was quite similar (55-57%)
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctoral of Philosophy in Environmental Engineering and Management Inter-University Program on Environmental Toxicology, Technology and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2009
Keywords: Organochlorine compounds; Pesticides -- Environmental aspects -- Thailand -- Chanthaburi Estuary; Pesticides -- Risk assessment -- Thailand -- Chanthaburi Estaury